Comparison of Brachial Compression Versus Ulnar Compression on Radial Artery Diameter: A Randomized Controlled Trial - Fatemeh Bahrami; Shayan Mirshafiee; Pejman Mansouri; Mohammadreza Eftekhari; Mohammad Vahidi; Fateme Baharvand; Ehsan Moradi Farsani; Hamed Vahidi (International Journal of Vascular Medicine)
Conclusion: Ulnar compression and brachial compression maneuvers demonstrated effectiveness in inducing radial artery dilation for a limited duration. These maneuvers may reduce the occurrence of access failure during radial artery cannulation. No significant differences were observed between the two maneuvers, indicating that they can be used interchangeably based on clinician preference. So, because the ulnar compression is simpler and more feasible for the patients, it can be considered instead of brachial compression.